GAMBARAN KADAR GLUKOSA DARAH SEWAKTU PADA LANSIA DI DESA ADAT TAMPUAGAN KECAMATAN KARANGASEM KABUPATEN KARANGASEM - nyoman mastra (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
Background: The aging process is a factor that causes a decrease in pancreatic function cells and insulin secretion in the elderly. As a result of this aging process, the risk of increased blood glucose levels and impaired glucose tolerance will be higher.Purpose: This study aimed to find out the description of random blood glucose levels in the elderly in the Traditional Village of Tampuagan, Karangasem District, Karangasem Regency.Method: The type of research used is descriptive research with simple random sampling techniques. The sample used 39 samples obtained through interviews and checking random blood gluc.ose levels while using the glucose oxidase method using the POCT toolResult: Obtained the highest random blood glucose levels of respondents who had normal random blood glucose levels. Based on characteristics found most in the age range of 60-74 years, female gender, and no history of DM.Conclusion: The description of blood glucose levels in the elderly in the Traditional Village of Tampuagan, Karangasem District, Karangasem Regency, mostly have normal blood glucose levels. Keywords: Random Blood Glucose, Elderly, POCT.